Konflikt interesov pri odobritvi kolektivne odškodninske tožbe, ki jo financira odvetniška družba - Fatur, Andrej (Podjetje in delo, 2024)
The paper examines the conflict of interest in the funding of a collective action for damages by the lawyer representing the claimant in the action and its impact on the certification of the action. The author starts by outlining the general rules governing the certification of collective actions for damages and the purpose of such certification. The author then introduces the conflict of interest inherent in lawyer-financing of collective actions for damages and applies this to the fulfilment of the representativeness test by each claimant through the prism of outsourcing the fulfilment of the representativeness conditions to a third party (or lawyer). The author then introduces the system of safeguards in the financing of collective actions and discusses the need for these requirements to be met in the case of lawyer-financing of collective actions for damages.
Keywords: agencijski problem; agency problem; certification of collective action; collective action for damages; conflict of interest; financing of collective action; financiranje kolektivne odškodninske tožbe; kolektivna odškodninska tožba; konflikt interesov; lawyer financing; odobritev kolektivne odškodninske tožbe; odvetniško financiranje; representativeness; reprezentativnost